Evaluation of the susceptibility to pigmentation of orthodontic esthetic elastomeric ligatures - Janine Soares Cavalcante; Marcelo de Castellucci e Barbosa; Marcio Costa Sobral (Dental Press Editora, 2013)
OBJECTIVE: The purpose of this laboratory study was to evaluate changes in the pigmentation of esthetic elastomeric ligatures after immersion in a staining solution. METHODS: Sixty ligatures were selected and divided into 12 groups according to their brand and also considering their condition, i.e., unstretched or stretched. The groups were divided into: Morelli (clear), TP Orthodontics (clear), American Orthodontics (clear), 3M/Unitek (clear), American Orthodontics (pearl color) and 3M/Unitek (pearl color), separated into groups of 5 unstretched and five stretched ligatures. Assessment of their color changes was performed by means of digital photograph and computer analysis using Adobe Photoshop. Standardized digital photographs were taken at T0 (before the staining process, with unstretched ligatures) and at T1 (following the 5-days staining process). The staining solution was composed of artificial saliva and foods with staining potential. At T1 the ligatures were either stretched or unstretched. RESULTS: The results of this study showed that esthetic elastomeric ligatures are prone to staining. Among the evaluated brands, TP Orthodontics and American Orthodontics clear ligatures were the most stable. Moreover, 3M/Unitek pearl ligatures demonstrated statistically significant changes in all variables. CONCLUSIONS: Esthetic elastomeric ligatures are susceptible to staining and no statistically significant difference was found between unstretched or stretched ligatures, with the sole exception of the TP Orthodontics brand. The 3M/Unitek's pearl color ligatures displayed the greatest staining potential.